Analisis Kepatuhan Regulasi Keamanan Pangan Produk Olahan Perikanan Melalui Identifikasi Label Kemasan - Belantika Amanda Permatasari; Jefri Anjaini; Lilik Setiyaningsih (Samakia : Jurnal Ilmu Perikanan, 2024)
Analysis of Food Safety Regulation Compliance for Processed Fishery Products through Packaging Label Identification, this study aims to understand the urgency of food safety regulations, evaluate producer compliance, and analyze packaging labels as indicators of compliance. Observations were conducted using a literature study method by collecting online data for five processed fishery products: sardines, fish floss, fish sauce, chikuwa, and fish oil. The results show that the five processed fishery product namely Sarden Gaga, Chikuwa Cedea, Bonroa Abon Ikan Cakalang, Finna Kecap Ikan, and OM3 Heart Natural Fish Oil—largely comply with BPOM Regulation No. 31 of 2018 and Government Regulation No. 69 of 1999, despite deficiencies in the inclusion of expiration dates and nutritional information. Four products have BPOM distribution permits, one has a PIRT permit, only Sarden Gaga complies with mandatory SNI standards, and two products do not display the halal logo as required by Law No. 33 of 2014.